The Psychological Impact of the Internet as a Source of Health Information - Ragil Tri Atmi; Dewi Naulifajrin (UPT Perpustakaan UIN Alauddin Makassar, 2023)
The internet is a source of health information for people in the digital age. By seeking health information through the internet, information seekers can seek the health information they need quickly and widely. In addition to the positive impact, the internet as a source of health information also has a negative impact on the seeker of information. The purpose of this article is to reveal the negative impact of utilizing the internet as a source of health information in the form of psychological impact. The method used is literature review. The findings of this article are that the internet has a psychological impact in the form of health anxiety. Information seekers who suffer from health anxiety tend to shut themselves off from people, lose concentration at work or study, withdraw from pleasant things, have poor relationships with health experts, drain money, and often feel anxiety symptoms. In response to this problem, information seekers need to equip themselves with digital literacy skills.